Urban climate and climate change - Kleerekoper, Laura (A+BE | Architecture and the Built Environment, 2016)
The industrial revolution brought us wealth and growth. The higher standard of life is now concerned as ‘basic’ in the western world and gradually increased the society’s dependency on highly exergetic energy resources. The combustion of these energy resources results in exhaust of fumes containing dangerous pathogens such as carbon monoxide, sulphur dioxide, nitrogen dioxide, benzene and formaldehyde (Perry, 2015). The effect on people’s health and the depletion of fossil fuels resulted in innovations to increase the efficiency of combustion and reduce harmful fumes. Today’s concern is especially focussed on the exhaust of particulate matter and the emission of CO2. The awareness on mitigation, preventing CO2 emissions in the atmosphere, started with the report of the World Commission on Environment and Development, which introduced the definition of sustainable development: “A development that meets the needs and aspirations of the present generation without compromising the ability of future generations to meet their needs” (Brundtland, 1987). The emission of CO2 influences the global climate, so much is clear by now: consensus about the relationship between CO2 emissions and global warming is very strong (IPCC, 2014b). Emissions from the past century are expected to already have an irreversible global warming effect that will especially affect the generation of our children and grandchildren. Effects often manifest on another location in the world than the places where most of the CO2 is emitted. Moreover, places that contribute less to high CO2 levels often have less means to protect themselves against climate hazards. Therefore, Machiel van Dorst added the importance of place to the Brundtland definition of sustainable development: “A development that meets the needs of here and now without compromising the ability of others to meet their own needs there and then” (Dorst, 2010). This chapter outlines the context of this research and answers the following research question: What is the impact of climate change on the urban environment in the Netherlands?